PLANIFICACIÓN ESTRATÉGICA PARA LA EMPRESA COMERCIAL ARMCERAMIC DE LA CIUDAD DE LOJA PARA EL PERÍODO 2016-2019 - Agila Saraguro, Johanna Alxandra (2017)
The Special Titling Unit work called "Strategic Planning for the Armceramic Commercial Company of the City of Loja for the Period 2016-2019", aims to make a strategic planning model aimed at formulating strategies for the achievement of business objectives through The most appropriate adjustment of the entity with its environment. This study will provide the necessary tools and basic for the owner-manager to properly manage the opportunities offered by the market and also prevent market fluctuations and technological advances from becoming strong threats. Of all this the survival of the company will depend in itself, of the capacity that the same one has to convert its resources and processes in strengths and not in weaknesses and vulnerabilities. As a first stage focuses on the fulfillment of the objectives set at the beginning of the work as General Purpose: strategic planning for ARMCERAMIC trading company of the city of Loja for the period 2016 to 2019 was performed in order to improve its economic system focused to a better competitive market development and specific objectives; the establishment of the mission statement, vision, objectives, policies and overall strategies of the organization for the period 2016-2019 as a point of image of the company as the second targeted a SWOT matrix is constructed by identifying the strengths and weaknesses of the entity and 6 should seize the opportunities and threats that should counter, so that the implementation of strategies to reach successfully accomplish; and the ultimate goal of design Strategic Objectives (Strategic Plan) as an alternative solution to the problems in Commercial Armceramic. The methodology used in the implementation of this work should be stressed that was initiated with the approach to the entity, through an interview with the manager - owner of the company Armceramic , and also with the information obtained through surveys conducted staff and customers of the same , allowed reaching an analysis of the current situation of the company resulting in the determination of internal factors (strengths and weaknesses) and likewise external factors (opportunities and threats) as determinants for development of strategic objectives. The main conclusions that you ended up determining work presently are the following ones: The company doesn't have a strategic planning as active part in the configuration of its future, since it acted as a remote entity of the reality not allowing him to be prepared to face the demands that he/she has the atmosphere of business at the present time, in the design of the Main FODA (Strengths, Opportunities, Weaknesses and Threats) it was identified that it exists big strengths like: To offer products of quality and to be legally constituted being satisfactory beginning for the company; but as for their weaknesses for nonexistence of strategic plans and still weak financial position does not allow you to expand your market 7 on a large scale; as for their opportunities they stand out: Faulty attention to the client for some companies competitors, expansion toward other commercialization areas with the purpose that the products have bigger welcome in the market and to increase the volume of sales by means of publicity and marketing existing starting point for the diversification of the company and monopolizing of great part of market, but also having a great meaning the threats like: Competitors' presence with lower prices, inflation and speculation and high taxes that it can affect in the acting of the company when going it by unnoticed, and that each one of these aspects was starting point for the formulation of strategies in order to improve the competitiveness, sustainability and, simultaneously to respond to the expectations of the interested parts.